Hots Assessment: Case Of Students' Performance On Understanding Of Statistical Graph - Adri Nofrianto; Elfa Rafulta; Mira Amelia Amri (EDUJAVARE: International Journal of Educational Research, 2026)
The study purpose is to assess senior high school students' ability on Higher Order Thinking Skills (HOTS) and understanding of statistical graph by using HOTS based statistical graph problems. The students were given two statistical graph problems. This research utilizes mixed-method research approach. It involves 42 senior high school students. The test result was analyzed based on two categories which are students' performance on solving HOTS based problem and students' understanding of statistical graph. The result suggested that (a) students that have good evaluation have higher rate of success on creating new version of graph based on their analysis; (b) students understanding of graph reading and graph interpretation is considered moderate and the main reason is students understanding of the graph properties itself; (c) Students found that constructing new graph is easier than evaluating graph; (d) Histogram chart is more difficult to construct by the students